(untitled) (Heritage, 2024)
In this paper, we analyze different Serbian prepositions that are used to express the simultaneity between events and processes. We explore both genuine temporal entities (like days, months, seasons) and happenings that presuppose the passage of time. Special attention is given to our conception of the passage of time, unlike the static nature of space. We have tried to give an account of the relation between the spatial and temporal usages of the prepositions na (on) related to the participation of the subject in activities and u (in) related to the state which is attributed to the subject or to the influence of some events on him. We also attempt to explain the need for creation of specific prepositions with exclusively temporal meaning prilikom (in the occasion of) and tokom (during) as well as the crucial differences between the ways they represent their arguments – in the first case as situations that are associated to some particular characteristics, or occasions in which take place some relevant events and in the second case as dynamic periods that coincide with some eventualities. Finally, we explain some specific usages of the basically spatial prepositions po (all over) – related to the meteorological conditions that accompany temporal entities, preko (over) - that expresses the placement of activities and state between its boundaries and pod (under) metaphorically representing the influence (in terms of domination) of the periods on the sentence subjects.